2020
DOI: 10.1038/s41598-020-75877-x
|View full text |Cite
|
Sign up to set email alerts
|

miRNA profiles of canine cutaneous mast cell tumours with early nodal metastasis and evaluation as potential biomarkers

Abstract: Cutaneous mast cell tumours (MCTs) are common skin neoplasms in dogs. MicroRNAs (miRNAs) are post-transcriptional regulators involved in several cellular processes, and they can function as tumour promoters or suppressors. However, the role of miRNAs in canine MCTs has not yet been elucidated. Thus, the current study aimed to characterize miRNA profiles and to assess their value as biomarkers for MCTs. miRNA expression profiles were assessed in formalin-fixed, paraffin-embedded samples by next-generation seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 66 publications
(84 reference statements)
0
12
0
Order By: Relevance
“…In the current study, the potential of saliva as a reliable minimally invasive biosample for the quantification of MCT-associated miRNAs in dogs was investigated for the first time. Three MCT-associated miRNAs, miR-21, miR-379, and miR-885, previously reported to discriminate between cutaneous MCT-affected and healthy dogs in formalin-fixed paraffin-embedded primary tumors, 34 was quantified in saliva samples of healthy and MCT affected dogs to investigate their potential as minimally invasive biomarkers. The three salivary miRNAs were quantified using a qPCR approach, and the results showed that only salivary miR-21 was modulated in the presence of the subcutaneous MCT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the current study, the potential of saliva as a reliable minimally invasive biosample for the quantification of MCT-associated miRNAs in dogs was investigated for the first time. Three MCT-associated miRNAs, miR-21, miR-379, and miR-885, previously reported to discriminate between cutaneous MCT-affected and healthy dogs in formalin-fixed paraffin-embedded primary tumors, 34 was quantified in saliva samples of healthy and MCT affected dogs to investigate their potential as minimally invasive biomarkers. The three salivary miRNAs were quantified using a qPCR approach, and the results showed that only salivary miR-21 was modulated in the presence of the subcutaneous MCT.…”
Section: Discussionmentioning
confidence: 99%
“…4 MiRNA-126 is up-regulated in some epithelial and nonepithelial neoplasms, like MCT, 7 and the amounts of miR-21, miR-379, and miR-885 in the tumor are able to predict the spread to lymph nodes in MCT-affected dogs. 34 Increased levels of miR-21 have been observed in the saliva of several cancer-affected human patients, suggesting its role as an oncomiRNA 19 promoting tumor progression. 3 The present study confirmed that miR-21 in the saliva of subcutaneous MCT-affected dogs is also higher compared with healthy and cutaneous MCT-affected dogs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The miRNAs profile of canine MCT has been previously characterized in formalin-fixed paraffin-embedded samples pointing out that a panel of three miRNAs, miR-21-5p, miR-379, and miR-885, have a good efficiency in discriminating healthy and MCT affected dogs, and MCT affected dogs with and without nodal metastasis, suggesting an epigenetic role in tumor progression ( 26 ). Recently, miR-21-5p has been identified as a potential biomarker in the saliva of MCT-affected dogs ( 27 ).…”
Section: Introductionmentioning
confidence: 99%